Pengaruh Metode Terapi Zikir dalam Mengontrol Halusinasi pada Pasien Skizofrenia di Ruang Rawat Inap Rumah Sakit Jiwa Aceh - Muhammad Baihaqi; Urip Pratama; Nurul Amna (Pusat Riset dan Inovasi Nasional, 2025)
Schizophrenia is a serious mental disorder with an increasing prevalence worldwide, which increases every year, making it a serious concern in the world. National surveys in mental health facilities indicate that nearly half of all clinical diagnoses involve hallucinations, precisely 49.77%. This investigation sought to evaluate the effectiveness of dhikr therapy as a means of moderating hallucinatory episodes in patients diagnosed with schizophrenia admitted to the inpatient section of Aceh Mental Hospital. By implementing a quantitative methodology with a pseudo-experimental design, the research adopted a one-group pre test–post test format. Out of 518 individuals who had hallucinations, only 15 participants were chosen as samples using purposive sampling considerations. Interventions in the form of dhikr therapy were carried out 5 times for 5 days, each lasting 20 minutes. The instruments used included the AHRS questionnaire to measure the level of hallucinations, it was found that the Alpha Coefficient = 0.607. The research took place during the period of March 17–21, 2025, and the dataset was processed using univariate and bivariate calculations, where the statistical method applied was the paired t-test. The results showed that out of 15 respondents before the administration of dhikr therapy, most experienced hallucinations in the moderate category of 8 respondents (53.4%) and after the administration of dhikr therapy, most experienced hallucinations in the mild category of 7 respondents (46.7%). Analysis results demonstrated that the p-value obtained was 0.000, smaller than the 0.05 standard, signifying that the application of dhikr therapy exerts a measurable effect in controlling hallucinations among schizophrenia sufferers. The findings conclude that the implementation of dhikr therapy provides a substantial contribution to the regulation of hallucinations in patients suffering from schizophrenia.